PENERAPAN MODEL UTAUT UNTUK MEMAHAMI NIAT MENGGUNAKAN SEARCH ENGINE ADVERTISING PADA PELAKU UMKM PROVINSI BALI - Dadas, Muhammad Azhari; Rahanatha, Gede Bayu (E-Jurnal Manajemen, 2019)
The purpose of this study was to examine the effect of performance expectancy, effort expectancy and social factor on intention to use search engine advertising. This research was conducted on UMKM in Bali province. Questionnaires became a means of collecting data in this study. The study sample was 75 respondents. The data processing technique in this study is Multiple Linier Regression (MLR). Based on the results of data processing it is known that performance expectancy has a significant positive effect on intention to use search engine advertising. Effort expectancy has no influence on intention to use search engine advertising. Social factor has a significant positive effect on intention to use search engine advertising. Keywords: performance expectancy, effort expectancy and social factor.